Synthesis of Monoclinic ZrO2-Supported Cu/ZnO for Methanol Production from Carbon Dioxide - Bol, omer Egemen; Behmenyar, Gamze; Akgun, Mesut (SPRINGER, 2025)
Methanol is produced via syngas, and the catalysts used are based on Cu/Zn/Al. There is no catalyst yet to produce methanol from carbon dioxide with high performance. In this study, zirconia-supported copper/zinc-based catalysts with gallium and lanthanum promoters were synthesized via incipient wetness impregnation (IWI), sol-gel (SG), and deposition-precipitation (DP) with various configurations. The samples were characterized via BET, SEM, H2-TPR, and XRD and tested for methanol production. On the BET analysis, the samples synthesized via DP method yielded the highest surface area with 51.282 m2/g. H2-TPR analysis showed that samples were reduced ideally at 250 degrees C. The incipient wetness impregnation method was found to have several disadvantages, while sol-gel and deposition-precipitation methods yielded uniformly dispersed oxide species on the support material, and the copper and zinc species' particle sizes strongly affected the catalytic performance of the sample as the XRD results indicated. The DP method gave the highest performance in producing methanol, and the 33Cu25Zn3Ga/MZ-DP catalyst sample acquired with the ideal amount of gallium addition as promoter was found to be giving the highest yield of methanol among all the samples (0.329 g gcatalyst-1 h-1) at 250 degrees C, 4 MPa, and 6000 h-1.
Keywords: Materials Science; Metallurgy & Metallurgical Engineering; Mineralogy; Mining & Mineral Processing